KONDYCJA FINANSOWA SAMORZĄDU TERYTORIALNEGO W POLSCE. PRZYCZYNY ZADŁUŻENIA I PROPOZYCJE REFORM - Osiński, Joachim; Zawiślińska, Izabela (Polityka i Społeczeństwo, 2021)
The authors aimed to examine the phenomenon of indebtedness on the part of the local self-government units in Poland. The situation is evolving, and as such it pertains to an overwhelming majority of municipalities and counties. The barrier to increased indebtedness was established in the form of a unit-specific debt indicator, which came into force in 2014, and the amendments came into existence on the 1st of January, 2020. The composition of the indicator aims to allow the Regional Chambers of Auditors to monitor the proceedings and prevent continued deterioration. However, the authors indicate that the crux of the issue that the local self-government units face is the insufficient revenue they generate, which calls for an increased allocation of central budgetary funds to the local selfgovernment units in the form of grants and subsidies as well as the designing of numerous ways to finance their operations. Drawing upon the experiences gained by other states, the authors postulate the launch of the territorial and resource-based consolidation reforms on the part of the lower local self-government units – municipalities. This is believed to enhance a more effective leveraging of the endogenous resources on the part of the local selfgovernment units, maximising the economies of scale that pertain to the local economy as well as societal resources. The lower local self-government units in Poland were established over 20 years ago. Since the establishment, the units have come to represent the entities that are ineffective in a structural and functional manner. Furthermore, they fail to ensure the modern development path of local communities. The examination that has been conducted validates the need for reforms and it portrays the currents behind.